TOWARDS AN INTEGRATIVE MODEL TO MANAGE RESISTANCE TO CULTURAL CHANGE - Wan Juli (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
This paper describe the development of an effective model in managing resistance to cultural change. The starting point of the description is the corporate culture, mainly its value and assumptions. It, then, shows the forms and manifestations of change manifestations and possible causes of the resistance. This paper addresses the change resistance issues by introducing two opposing views and their limitations. The first view, the cause-driven model, argues that the strategies to overcome resistance depend on its causes. The main limitation of this model is that it fails to acknowledge the multidimensional aspects of change. On other hand, the systematic view asserts that resistance is unchangeable and that the best method is to work with resistance rather than to overcome or beat the resistance. However, this model tend to ignore the individual aspects of resistance. I would argue that the best model should be the combination of both models. The suggested model consists of six steps: building a shared mission, communicating the mission-based change agenda, encouraging the employees’ participation, building trust through dialogue, and institutionalising the cultural change. However, this model has three major limitations. Firstly, the implementation of the model should be integrated with the other change programs. Another limitation relates to the assumptions of this model (time availability, information needed, and resistance power). The last limitation is that this model undermines the stress and high tension.